Huge Cystic Lymphangioma of the Pancreas Mimicking Pancreatic Cystic Neoplasm - Enrico Dalla Bona; Valentina Beltrame; Stella Blandamura; Federica Liessi; Cosimo Sperti (Case Reports in Medicine)
Lymphangiomas of the pancreas are very rare benign tumors of lymphatic origin, accounting for less than 1% of these neoplasms. We report a case of a 55-year-old woman who presented with a palpable mass in the left abdomen. Abdominal sonography and computed tomography showed a lobulated, hypodense mass extending from the left diaphragm to the pelvis, measuring  cm. A preoperative diagnosis of mucinous cystadenoma of the pancreas was suggested and the patient underwent laparotomy. Distal pancreatectomy with splenectomy was performed, encompassing a segment of descending colon because of close relationship to the mass. The cystic mass was histologically diagnosed as lymphangioma of the pancreas. The patient is well and free of disease 12 months after surgery. Pancreatic lymphangioma should be kept in mind when a huge, multiloculated mass is encountered in the abdomen, especially in adult women. Although lymphangioma is considered a benign tumor, involvement of adjacent organs sometimes occurs and extended resection is required to obtain a radical treatment.